Timing Analysis of Algorithm Substitution Attacks in a Post-Quantum TLS Protocol - Marchiori, Dúnia; Giron, Alexandre A.; Nascimento, João Pedro A. do; Custódio, Ricardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2021: Anais do XXI Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2021.17311, 2021)
Snowden's revelations about mass surveillance brought to public attention devastating attacks on cryptographic algorithm implementations. One of the most prominent subsets of these attacks is called Algorithm Substitution Attacks (ASA), where a subverted implementation leaks sensitive information. Recently, it has been proposed to modify TLS implementations to use Post-Quantum Cryptography (PQC). In this paper, we propose and analyze ASA in two PQC schemes that can be used in TLS. We attacked the Kyber Key Encapsulation Mechanism (KEM) and Falcon Signature and successfully deployed them in a TLS implementation. Results show that timing analysis can distinguish our Falcon subversion, but it is not enough to detect our attacks deployed in TLS.